Beliefs and Practices of Patients with Diabetes toward the Use of Herbal Therapy - Besher Gharaibeh; Loai Tawalbeh (AIMS Press, 2018)
This study aimed to assess the prevalence of using herbal therapy and the beliefs toward the use of this type of therapy among patients with diabetes. It also aimed to identify the significant predictors of these beliefs and the factors that increase the likelihood of using herbal therapy. A descriptive cross-sectional design was used. A convenience sample comprised 310 patients with diabetes. Sixty-seven (21.6%) of the participants used herbal therapy. The mean beliefs score was 3.72 and ranged from (0-12). Linear regression showed that beliefs were significantly predicted by self-care, attending workshops, education level, and number of complications. The logistic regression showed that the lower the self-care and the higher the beliefs, the more likelihood the patient uses herbal therapy. Informing patient through individualized diabetes education influences the patient's beliefs and promotes self-care. This education program should target mainly those patients with low self-care, high number of complications, lower educational level and having more complications.